2019
DOI: 10.1029/2018jd029703
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Potential Nitric Acid Removal During Convective Injection of Water Vapor Over the Central United States on the Chemical Composition of the Lower Stratosphere

Abstract: Tropopause‐penetrating convection is a frequent seasonal feature of the Central United States climate. This convection presents the potential for consistent transport of water vapor into the upper troposphere and lower stratosphere (UTLS) through the lofting of ice, which then sublimates. Water vapor enhancements associated with convective ice lofting have been observed in both in situ and satellite measurements. These water vapor enhancements can increase the probability of sulfate aerosol‐catalyzed heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 158 publications
(283 reference statements)
0
4
0
Order By: Relevance
“…water vapour budget in the atmosphere, impact the exchange processes between the troposphere and stratosphere, and affect the surface energy balance (Roewe and Liou, 1978;Berry and Mace, 2014;Dessler et al, 2016). Although difficult to observe, the presence of SICs has been found and discussed in a number of studies (Clodman, 1957;Sandhya et al, 2015). However, due to the intricacy of atmospheric processes, the precise mechanisms for the formation and existence of SICs under different atmospheric conditions are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…water vapour budget in the atmosphere, impact the exchange processes between the troposphere and stratosphere, and affect the surface energy balance (Roewe and Liou, 1978;Berry and Mace, 2014;Dessler et al, 2016). Although difficult to observe, the presence of SICs has been found and discussed in a number of studies (Clodman, 1957;Sandhya et al, 2015). However, due to the intricacy of atmospheric processes, the precise mechanisms for the formation and existence of SICs under different atmospheric conditions are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence for the existence of SICs at midlatitudes was found from in situ measurements (Murgatroyd and Goldsmith, 1956;Clodman, 1957;Bartolome Garcia et al, 2021), ground-based lidar observations (Keckhut et al, 2005;Noël and Haeffelin, 2007), and satellite data (Spang et al, 2015;Homeyer et al, 2017). Sassen and Campbell (2001) showed that about 5 %-7.5 % of cirrus cloud tops are located above the tropopause over Salt Lake City, Utah, in the winter season based on a 10-year high cloud data set at the University of Utah Facility for Atmospheric Remote Sensing.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction efficiency of HCl+ClONO 2 can be affected not only by different types of surfaces (e.g., organic aerosols and PSCs), but also by water vapor content and pressure, which vary with altitude ( 34 ), which has been suggested as a potential midlatitude ozone depletion mechanism ( 35 , 36 ). We therefore expand the focus to the range of altitudes from 14.5 to 18.5 km for 2020, 2021, and 2012 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Midlatitude ozone is mainly affected by an increase in heterogeneous chemistry, which increases ClO x (= Cl + ClO + 2 • Cl 2 O 2 ) and reduces NO x (= NO+NO 2 +NO 3 +2•N 2 O 5 ) (Pitari et al, 2014;Heckendorn et al, 2009). The increase in ClO x , which causes ozone destruction in the ClO x cycle (Stolarski and Cicerone, 1974;Rowland and Molina, 1975), is balanced by the reduction in NO x , which reduces ozone destruction in the NO x cycle (Crutzen, 1970;Johnston, 1971), until the middle of this century (Pitari et al, 2014). In the subsequent decades, the decrease in ODSs would result in a general increase in stratospheric ozone (Pitari et al, 2014).…”
mentioning
confidence: 99%